Temporal and Spatial Variations of the Solar Radiation Observed in Singapore - Jayaraman, Ramkumar (2016)
Meteorological phenomena, such as fast moving clouds, cause rapid changes in the terrestrial direct beam radiation. This introduces transients in both the temporal and spatial measurements of global horizontal radiation. These transients in radiation affect the performance of solar energy conversion systems (PV, CPV systems and solar thermal applications) and cause their output power to vary widely. Thus, to properly understand the dynamic fluctuations observed in the output energies of large solar farms and PV arrays, it becomes necessary to perform a high-resolution temporal and spatial measurement of solar radiation. It turns out that performing such high-resolution measurements is often cost-prohibitive. Studies were conducted to understand and quantify the temporal and the spatial variations of direct beam, diffused and global horizontal radiation. These studies were based on the radiation data collected at the Nanyang Technological University, Singapore at a time interval of 1 s. It was inferred from these studies that the temporal variations in the instantaneous diffuse radiation are minimum and there was little spatial variations seen across distances of 500 m. The transients observed in global horizontal radiation are predominantly restricted to the changes occurring in the direct beam component of the solar radiation. Based on these inferences, a simple and costeffective method is proposed that would permit accurate large scale localised high-resolution measurements of individual components of the solar radiation.